The Role of Special Libraries to Fulfill the Requirement of Industrial Information of Small and Medium Scale Industrial Sector in Western Province - Wijekoon, K.S.C.; Wijekoon, W.A.S. (University of Sri Jayewardenepura, Nugegoda, 2015)
Industrial sector plays an important role in the economic development of the country. It consists of medium and small industries which contributes 90 % to the industrial sector in Sri Lanka and considered as the mechanism of economic development Small and medium industries have been defined as the industries where the annual turnover is below 900 and employment is below 300. The main objective of the study is to start new industries and evaluate the service of five (5) selected libraries. Impact of Industrial information is vital and timely to study its role and productivity of such a service. N e w technological knowledge needed for the development of industries, potentials of entrepreneurs, potential of expanding capacity in Sri Lanka were specially studied in this study. In addition, an analysis has been made with regard to the aspects which should be further improved on behalf of service beneficiaries. This is a positivist study. One structured and another non-structured questionnaires, organized and unorganized interviews were used and observations and case-studies, etc. were applied. Out of the 52 libraries in Colombo district, only 5 were selected for the study. Sampling units were the individual customers w h o came to get the service from these libraries and 5 librarians. According to the survey, 64% of the customers used libraries to obtain information to start new industries and 20 to obtain information to improving their industries. Main weaknesses found w ere the unavailability of new technological information and updated information on small and medium industries. Out of the total number of customers, 43% were using libraries to obtain information on food-related industries. In addition, an active contribution of both government and non-governmental policy makers is essential in this connection. The conclusions and recommendations of this study are useful for all w h o are directly and indirectly engaged in the industries in Sri Lanka.
Keywords: economic development; employment; entrepreneurship; industrial development; small and medium scale industries; special libraries